Draft Five Year Plan 1978-83 Technical Education Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
Technical Education provides nucleus for all developmental activities. It goes without saying that success of all major sectors of a developing economy depends on the efficiency, availability & quality of manpower. In the context of the economic and industrial development of our country, technical education has assumed even greater importance and this sector of development had, in the past, been given the importance it really deserved.
Government of Madhya Pradesh, Planning, Economics and Statistics Department